Effect of the static pressure on the power dissipation of gearboxes. (13th August 2019) - Concli, Franco; Gorla, Carlo; Rosa, Francesco; Conrado, Edoardo
Abstract: Many researches were conducted in the past in order to maximise the efficiency of gearboxes, and for many of the sources of power loss, very effective models and tools are already available and can significantly help to optimise the design. Nevertheless, for the load‐independent power losses of gears only in the recent years some progress has been made. Concerning these losses, numerical simulations can help the designers in optimising the internal shape of the casing, thus ensuring the proper lubrication of all the components and reducing the undesired splashing losses. The amount of lubricant plays a fundamental role: A reduction of the lubricant can be critical from the point of view of adequate lubrication and of failures of the system due to wear, scuffing, and pitting but, on the other side, an excessive amount of lubricant leads to additional power dissipation and could even determine an overheating of the system. Another possibility to improve efficiency could be represented by the reduction of the pressure inside the housing: in this paper, the effect of the static pressure on the load‐independent power losses both for complete‐ and dip‐lubrication has been deeply studied. The numerical results, validated by experimental data, show that a reduction up to 15% of the churning losses can be achieved without reducing the amount of lubricant, that is, without increasing the risk of failures related to lubrication. Based on the results obtained, the reduction of the pressure of the housing proves to be a way to improve the efficiency, provided the related engineering issues are also addressed.